ANALISIS HASIL BELAJAR SISWA MELALUI PEMBELAJARAN DENGAN MODEL AWARENESS TRAINING TERINTEGARSI NATURE OF SCIENCE - Zamzuri, Aliman Ro'yun; Hadi, Wiwin Puspita; Tamam, Badrud; Putera, Dwi Bagus Rendy Astid; Rakhmawan, Aditya (Natural Science Education Research, 2023)
This study aims to determine differences in learning outcomes between the control and experimental classes by using the integrated nature of science awareness training learning model. This research uses Quasi Experimental Design with Nonequivalent Control Group Design. This research was conducted at SMP Al-Kholiliyah Bangkalan using a simple random sampling technique, so that the sample used was 20 students in each class. The learning achievement test is based on Bloom's taxonomy with cognitive levels C1 to C6 in the form of an essay totaling 6 questions. The hypothesis analysis technique uses the free sample t test. based on the results of the study it can be concluded that: 1. The learning model of awareness training integrated with nature of science has an effect on student learning outcomes, as evidenced by the results of the free sample t test obtained a significance value of 0.000 less than 0.05, then H0 is rejected and H1 is accepted. 2. The test results for the experimental class were better than the control class with an average score of 58.35 for the experimental class, while for the control class it was 24.95 with a percentage difference of 57,41%.